2013
DOI: 10.1149/2.116308jes
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spiral Flow Field Design on Performance and Durability of HT-PEFCs

Abstract: The geometries of flow fields have a strong impact on gas distribution in fuel cells. In the present work, a series of customized spiral flow fields were applied to high-temperature polymer electrolyte fuel cells. Pressure tests revealed that a flow crossover occurred in the spiral flow field under consideration, which was caused by the pressure difference between two adjacent channels. Electrochemical characterization indicated that the modified gas distribution compensated the O2 depletion along the channel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…The MEAs were assembled inside the cell without a preceding hot-pressing step. Graphitic flow field plates with machined threefold serpentine structure were used [15,16]. The stainless steel end plates were heated to adjust the operating temperature.…”
Section: Mea and Cell Preparationmentioning
confidence: 99%
“…The MEAs were assembled inside the cell without a preceding hot-pressing step. Graphitic flow field plates with machined threefold serpentine structure were used [15,16]. The stainless steel end plates were heated to adjust the operating temperature.…”
Section: Mea and Cell Preparationmentioning
confidence: 99%
“…The increase in catalyst particle size was observed to occur during two longterm experiments. Liu et al [23] showed that flow channel design greatly affects the performance and stability of HTPEMFCs.…”
Section: Introductionmentioning
confidence: 99%
“…A second series of studies [19,20,21,22,23] used CFD techniques to simulate full 3D PEMFCs. These studies examined polarization curves, pressure drops, and a number of cell design parameters.…”
Section: Introductionmentioning
confidence: 99%